Meaning Resilience dalam Perspektif Pendidikan Islam Telaah Konseptual di Tengah Krisis Eksistensial Modern - Rizkiah Kasim; Muh. Mukmin Passa; Patma Patma (Jurnal Studi Pendidikan Agama Islam, 2025)
The development of modern society, characterized by technological advances, rapid social change, and the dominance of instrumental rationality, has given rise to an existential crisis in the form of a void in the meaning of life, especially among the younger generation. This condition poses a serious challenge to the world of education, which tends to be oriented towards cognitive achievement and academic performance, while the dimension of the meaning of life receives less attention. This study aims to examine and conceptualize meaning resilience as a response to the existential crisis from the perspective of Islamic education. This study uses a qualitative approach with a literature review through conceptual analysis and content analysis of various literature relevant to the themes of meaning of life, resilience, and Islamic education. The results of the study show that Islamic education has a strategic role in building resilience of meaning through the integration of the values of tawhid, strengthening the orientation of life goals, and the holistic internalization of spiritual, moral, and intellectual values. Meaning resilience in Islamic education not only functions as psychological resilience but also as an existential capacity that enables individuals to interpret the reality of life in a meaningful and goal-oriented manner. Thus, Islamic education has the potential to become a transformative educational paradigm capable of shaping individuals who are resilient, meaningful, and ready to face the complexities of life.